2019
DOI: 10.12998/wjcc.v7.i4.405
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitor-induced colitis: A comprehensive review

Abstract: Immune checkpoint inhibitors (ICIs) are monoclonal antibodies that target down-regulators of the anti-cancer immune response: Cytotoxic T-lymphocyte antigen-4, programmed cell death protein-1, and its ligand programmed death-ligand 1. ICIs have revolutionized the treatment of a variety of malignancies. However, many immune-related adverse events have also been described which mainly occurs as the immune system becomes less suppressed, affecting various organs including the gastrointestinal tract and causing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
217
2
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(231 citation statements)
references
References 83 publications
5
217
2
7
Order By: Relevance
“…Immunotherapy using immune checkpoint inhibitors (ICIs), which can interrupt the cancer-immunity cycle and promote the tumor-specific immune cell activity without intrinsic cytotoxicity, has become the standard of care for a variety of tumors, including melanoma, lung cancer, urothelial cancer, kidney cancer, and hepatocellular carcinoma (HCC) [1][2][3][4][5][6][7][8][9][10][11][12]. For HCC patients, increasing importance has been attached to liver transplantation (LT) thanks to the advances in surgical techniques and immunosuppression regimens, resulting in the mean 1-year and 5-year survival rates of 85-90% and 70-75%, respectively [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy using immune checkpoint inhibitors (ICIs), which can interrupt the cancer-immunity cycle and promote the tumor-specific immune cell activity without intrinsic cytotoxicity, has become the standard of care for a variety of tumors, including melanoma, lung cancer, urothelial cancer, kidney cancer, and hepatocellular carcinoma (HCC) [1][2][3][4][5][6][7][8][9][10][11][12]. For HCC patients, increasing importance has been attached to liver transplantation (LT) thanks to the advances in surgical techniques and immunosuppression regimens, resulting in the mean 1-year and 5-year survival rates of 85-90% and 70-75%, respectively [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…nivolumab) have a risk of 1.3%-2.9%. Other classes of ICPIs such as anti-CTLA-4 and anti-PD-L1 showed a risk of 7.0%-11.6% and 0.7%-19.7% [4]. When comparing anti-PD-1 inhibitors to the other class of ICPIs, the frequency and severity of colitis seem to be lower.…”
Section: Discussionmentioning
confidence: 91%
“…The Common Terminology Criteria for Adverse Events (CTCAE) are a set of criteria used to classify the adverse effects of drugs in clinical trials including cancer therapy. Based on the CTCAE grading (severity) scale, the treatment options may vary from the symptomatic treatment of diarrhea with loperamide and electrolyte repletion to the initiation of immunosuppressive agents [4]. In the case of refractory colitis, multiple studies have shown a response to infliximab, mycophenolate, cyclosporine, and Entyvio [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Immunassoziierte Kolitidenund Diarrhöensind hĂ€ufigeirAEs und treten spĂ€ter, meist etwa 5 bis 10 Wochen nach der zweiten oder dritten ICI-Gabe, als dermatologische irAEs auf [15]. Abb.…”
Section: Gastrointestinale Manifestationunclassified